Visuaalisen brändikokemuksen suunnitteluohjeet digitaalisissa alustoissa - Kotilainen, Helene (2024)
Digitization creates new pressures for companies to produce successful products and engage consumers in an online environment. Creating the experience of trust plays a major role when building consumer commitment, as well as positive user experience and successful brand management. The brand experience is built through different senses while consumer is interacting with company´s different touchpoints such as through digital platforms, where sight is the most dominant and significant interacting sense. Therefore, visual aesthetic and understanding its design are major key factors in creating a successful brand experience. There is a huge variety of design guidelines to support design, which can be found in different kind of non-scientific sources. The term “brand experience” is used holistically when talking about the factors affecting the brand experience, even if the experience is created by the stimulation of the consumer's visual sense only. Thus, it is unclear what kind of visual brand experience design guidelines exist and are they based on any kind of scientific theories or arguments, or whether they are built entirely based on intuition. Design guidelines for visual brand experience and understanding their scientific background would help designers to create more significant and successful design solutions on digital platforms. In this master's thesis research was made on visual brand experience design guidelines, do they exist, whether it is possible to classify them into different categories and what kind of psychological theories or scientific arguments are they based on. The research used systematic literature review methodology that was based on the PRISMA statement to ensure a systematic, transparent procedure throughout the research process. The purpose of the research is to help designers and those involved in the design process in finding, categorizing, and critically examining design guidelines for the visual brand experience. The study combines previous studies on the visual brand experience related topics and how visual brand experience design guidelines could possibly be studied in the future. The research results showed that precise, practical, scientific research based visual brand experience design guidelines have not been built, but there are guidelines, evaluation models and frameworks that can be used to support the visual brand experience design process.